2013
DOI: 10.1590/s0100-736x2013001200011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos epidemiológicos da Doença de Chagas canina no semiárido paraibano

Abstract: Com o objetivo de determinar os aspectos epidemiológicos que envolvem a doença de Chagas (DC) canina e identificar os principais fatores de risco da enfermidade no semiárido paraibano, foi conduzido um estudo na zona rural de Patos, onde a área foi dividida em três estratos amostrais (Norte, Sul e Oeste) e, em cada estrato foram amostradas aleatoriamente 294 casas, e dessas todos os cães domiciliados representaram as unidades elementares do estudo. Em cada unidade domiciliar foi aplicado um questionário epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
0
7
0
2
Order By: Relevance
“…(2013) 26 with dogs naturally infected by Trypanosoma cruzi showed a prevalence of 4.08% in the rural area of the municipality of Patos , located in the semiarid region of the nearby Paraiba State, a significantly lower prevalence in comparison with that found in SJPI (7.7%). The contextualization of the problem and the production of data on these diseases in the municipality of SJPI will bring a better understanding of epidemiological issues and pertinent entomological, political and administrative discussions.…”
Section: Discussionmentioning
confidence: 95%
“…(2013) 26 with dogs naturally infected by Trypanosoma cruzi showed a prevalence of 4.08% in the rural area of the municipality of Patos , located in the semiarid region of the nearby Paraiba State, a significantly lower prevalence in comparison with that found in SJPI (7.7%). The contextualization of the problem and the production of data on these diseases in the municipality of SJPI will bring a better understanding of epidemiological issues and pertinent entomological, political and administrative discussions.…”
Section: Discussionmentioning
confidence: 95%
“…This value differs from that (22.7%) described by Souza et al (2009), which analyzed the seroprevalence of T. cruzi infection in dogs from Mato Grosso do Sul using IFAT and ELISA. Mendes et al (2013) found a prevalence of 4.08% using IFAT, ELISA and indirect hemagglutination (IHA), in Patos, PB. The higher frequencies could probably be attributed to the predominantly rural survey areas, which are the usual ecotopes of disease vectors.…”
Section: Discussionmentioning
confidence: 99%
“…and T. cruzi, with antibody titer levels of 1:40 and 1:80, respectively, indicating no greater discrepancies between titers. The state of Paraiba is endemic for CVL and presents confirmed cases of CD in dogs (BRITO et al, 2016;MENDES et al, 2013). Luciano et al (2009), who used IFAT to evaluate cross reactions between Leishmania spp.…”
Section: Epidemiologicalmentioning
confidence: 99%